A linear matrix inequality-based extended dissipativity criteria for linear systems with additive time-varying delays. (30th December 2019) - Gnaneswaran, Nagamani; Joo, Young Hoon; Kim, Han Sol
Abstract: In this paper, the problem of extended dissipativity performance has been investigated for a class of linear systems with additive time-varying delays. By constructing an appropriate Lyapunov Krasovskii functional (LKF) with triple and quadruple integral terms, a delay dependent extended dissipativity criterion which specifies H ∞, dissipativity, passivity and l 2 − l ∞ performance has been established. The obtained delay derivative dependent extended dissipativity results have been presented in terms of linear matrix inequalities (LMIs) which can be efficiently solved via some standard numerical softwares. Finally, some numerical examples are provided to verify the effectiveness of the presented results.